2014
DOI: 10.1002/bdra.23333
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence for Potential Harm of Electronic Cigarette Use in Pregnancy?

Abstract: Background Use of electronic cigarettes (e-cigarettes) and other nicotine containing products is increasing among women of reproductive age. The short- and long-term effects of these products on both mother and fetus are unknown. Methods Because e-cigarettes are nicotine delivery systems, we sought to conduct a comprehensive review of the effects of nicotine on the fetus. Results In utero nicotine exposure in animal models is associated with adverse effects for the offspring lung, cardiovascular system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 85 publications
1
59
0
2
Order By: Relevance
“…Until now, there is lack of evidence whether NRT – regardless of the method of administration – is effective or safe when used to promote smoking cessation in pregnancy or whether it has positive or negative impacts on pregnancy outcomes. Therefore, further research on the efficacy and safety of NRT during pregnancy is needed, in particular evidence from placebo‐controlled RCTs investigating higher doses of NRT than those already tested in previous studies [31,32]. The use of bupropion and varenicline is contraindicated during pregnancy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there is lack of evidence whether NRT – regardless of the method of administration – is effective or safe when used to promote smoking cessation in pregnancy or whether it has positive or negative impacts on pregnancy outcomes. Therefore, further research on the efficacy and safety of NRT during pregnancy is needed, in particular evidence from placebo‐controlled RCTs investigating higher doses of NRT than those already tested in previous studies [31,32]. The use of bupropion and varenicline is contraindicated during pregnancy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use behavior among pregnant women includes cigarette and electronic cigarette smoking [19-21] and smokeless tobacco use [22,23]. These tobacco-related behaviors, as well as second hand smoke exposure [24] remain prevalent in the perinatal population, with 16% of pregnant women reporting smoking [1].…”
Section: Tobaccomentioning
confidence: 99%
“…Nicotine, the dependence‐producing drug in ECIGs, is a toxicant of particular concern for pregnant women, as nicotine is known to harm a fetus (e.g., Bruin, Gerstein, & Holloway, ; England et al, ) some have suggested that no amount of nicotine in pregnancy is safe (CDC, ; Suter, Mastrobattista, Sachs, & Aagaard, ). ECIGs differ dramatically in terms of their nicotine delivery, with some products delivering little to no nicotine (e.g., Farsalinos et al, 2014; Vansickel et al, 2010; Yan & D'Ruiz, 2015), and others delivering as much, or more, than a combustible cigarette (e.g., Ramoa et al, 2016; St. Helen, Havel, Dempsey, Jacob III, & Benowitz, ; Wagner et al, ).…”
Section: Do Ecigs Deliver Nicotine and Other Toxicants?mentioning
confidence: 99%